Análise da segurança no trabalho no setor de mármore e granito do Espírito Santo: proposição de ação para reunião do índice de acidentes no trabalho - Cavalcanti, Hebert de Almeida (2001)
The granite and marble sedor of Espírito Santo is the biggest Brazilian industrial pole, being a leader in marketing its derived products, both in the domestic and externai markets. Despite the significant growth in the export values in the last years, in weight and values, as well as a higher value-added in the products marketed each year, the sector has still to live with problems of several natures that, if solved, will allow a bigger market share in the markets where it actuates. In the social aspects the benefits will be immediate, because the induced investments will generate a significant number of labor posts considering that the adivity is highly job generating. On the other hand, the benefits arising from the expected production increase will generate income and hard currency for the country. Among the problems to be solved is the high accident index in the sector, as shown by the statistical figures presented in this paper. The goal of this work is to establish actions aiming at the reduction of such indexes, having as a main target the safeguarding of the worker's health and safety. This will generate produdivity gains and costs reduction as a natural consequence, considering that accidents imply in additional costs. The globalization of the economy and the current economic policies of the country, have made the economic sectors compete more fiercely, forcing them to search for alternatives that make them feasible. The reduction of costs through labor accidents prevention constitutes one of these alternatives. This paper presents the accidents occurrences tendencies, arising from a diagnosis made at the activities of the sector, i.e. quarrying, sawing and finishing, if IX in the future, nothing is done. A comparison is made with ali other sectors of the capixaba economy, taking into account their own tendency curves, by which the seriousness of the situation and the importance of the reduction of accidents in the marble and granite sector of Espírito Santo is evidenced. Taking into consideration the dimension presented by the problem, the need for interventions arise, which are classified as immediate and of medium term interventions. The abiding to the current legislation, represented by the Regulatory Rules, will provide more safety to the workers, allowing them to perform their activities in an environment where the risk of injuries, with or without time loss, and death, will be minimized, considering that these hazards are inherent to the sector and will always be present. As methodology, field interviews with businessmen, workers, businessmen and workers' unions, representatives of DRT (Labor regulatory board) and INSS(Social Security) are used, with whom it is possible to make the statistical appraisal possible and the reading of specialized magazines, newspaper, Internet, papers and Regulatory Rules. The theoretical reference of several authors is also used, in the search of the conceptual basis to the subject. As result, a proposal is presented constituting of several actions to be implemented for the achievement of the desired goal.